2017
DOI: 10.3892/ol.2017.5809
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products influence oral cancer cell survival via Bcl-xl and Nrf-2 regulation in vitro

Abstract: Abstract. An irreversible non-enzymatic reaction between carbohydrates and proteins results in the formation of advanced glycation end products (AGEs). AGEs have been demonstrated to be a risk factor of complications in patients with diabetes mellitus (DM). Previous studies have suggested that patients with DM exhibit a higher rate of metastasis of oral cancer and a lower cancer-associated survival rate. The receptor for AGEs (RAGE) has been associated with angiogenesis and an increase in cancer malignancy. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…The reduction of MMP-9 activity by resveratrol is related to the suppression of the phosphorylation of ERK and JNK induced by TPA [115]. Using the oral cancer cell line SAS, it was observed that resveratrol induces apoptosis through nuclear factor-erythroid 2-related factor 2, heme oxygenase 1, tumor protein p53 and Bax signaling pathways [117].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The reduction of MMP-9 activity by resveratrol is related to the suppression of the phosphorylation of ERK and JNK induced by TPA [115]. Using the oral cancer cell line SAS, it was observed that resveratrol induces apoptosis through nuclear factor-erythroid 2-related factor 2, heme oxygenase 1, tumor protein p53 and Bax signaling pathways [117].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…The formed AGEs enhance cancer cell migration through the expression of vascular endothelial growth factor (VEGF), NF-κB, and extracellular signal-regulated kinase (ERK) pathways [13,21]. AGEs-RAGE axis has induced cancer cell progression in colon, breast, oral, prostate, and neuroblastoma cell lines (Table 1), and AGEs-RAGE axis can enhance cancer progression through regulation of the pathways and molecules described below and illustrated in Figure 1 [21][22][23][24][25][26][27]. The effects of receptor for advanced glycation end product (RAGE)-ligands on cancer progression.…”
Section: Mechanisms Of Ages-rage Axis Cancer Progressionmentioning
confidence: 99%
“…Nuclear factor (erythroid-derived 2)-like 2 (Nrf-2): Keap1 complex could lead to cancer cell proliferation and metastasis through regulation of p53 apoptotic pathway [23,40]. Activated AGEs-RAGE axis in oral cancer (SAS) cell line led to downregulation of Nrf-2 that consequently facilitated the spread of cancer cells [23]. The authors postulated that downregulation of Nrf-2 is associated with the downregulation of p53 of oral cancer cells via heme oxygenase (HO-1).…”
Section: Nrf-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Az áttétképződésben szerepet játszik a DM-ben megemelkedett mátrixmetalloproteináz-szint is [8,18]. Tartósan magas vércukorszint esetén emelkedik a glikációs végtermékek szintje és ennek révén a RAGE (receptor for advanced glycation end products) expressziója, amely a carcinomák invazivitásának szabályozójaként elősegíti a tumorszóródást [19,20]. A hyperglykaemia hatására fokozódik a vér alakos elemeinek agglutinációja, amely microembolisatio révén érelzáródást és ennek következtében szöveti hypoxiát okoz [21,22].…”
Section: Megbeszélésunclassified